2006
DOI: 10.1074/jbc.m605101200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DNA Modifications on DNA Processing by HIV-1 Integrase and Inhibitor Binding

Abstract: Integration of the viral cDNA into host chromosomes is required for viral replication. Human immunodeficiency virus integrase catalyzes two sequential reactions, 3-processing (3-P) and strand transfer (ST). The first integrase inhibitors are undergoing clinical trial, but interactions of inhibitors with integrase and DNA are not well understood in the absence of a co-crystal structure. To increase our understanding of integrase interactions with DNA, we examined integrase catalysis with oligonucleotides contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…In the case of the WT IN, removing either of these two bases flanking the 3′-P site (positions +1 and −1) markedly reduced 3′-P while enabling RAL and DTG to inhibit 3′-P almost as efficiently as ST. An important difference between the SH and the WT enzymes, with respect to the viral DNA interactions (Figures 1 and 2) is our finding that the +1 guanine base (immediately 3′ from the conserved CA; see Figure 1A) is critical for optimum 3′-P activity in the case of the WT IN (34,45,46). By contrast removing this +1 guanine enables the SH mutant to regain 3′-P activity.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the case of the WT IN, removing either of these two bases flanking the 3′-P site (positions +1 and −1) markedly reduced 3′-P while enabling RAL and DTG to inhibit 3′-P almost as efficiently as ST. An important difference between the SH and the WT enzymes, with respect to the viral DNA interactions (Figures 1 and 2) is our finding that the +1 guanine base (immediately 3′ from the conserved CA; see Figure 1A) is critical for optimum 3′-P activity in the case of the WT IN (34,45,46). By contrast removing this +1 guanine enables the SH mutant to regain 3′-P activity.…”
Section: Discussionmentioning
confidence: 91%
“…First, we compared the 3′-P activity of WT IN on a DNA substrate with the canonical CAGT sequence to the 3′-P activity on a substrate containing an abasic site at the −1 position relative to the cleavage site on the scissile strand (C_GT or 21Ab-1, Figure 1A). The conserved adenosine at the -1 position is known to be important for the activities of IN (34–37). Accordingly, 3′-P of this 21Ab-1 DNA was markedly reduced (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probing effects of various DNA backbone, base, and groove modifications on IN catalytic activities suggested that IN requires flexibility of the phosphodiester backbone at the scissile bond [75]. The other study examined 2′-modified nucleosides and 1,3-propanediol insertions in various positions of the U5 sequence [76].…”
Section: Sequence and Structure Of Viral Dnamentioning
confidence: 99%
“…All drug solutions were prepared from powder in 100% dimethyl sulfoxide. Drug concentrations producing 50% inhibition (IC 50 values, Table 1) are from previous reports Di Santo et al, 2006;Johnson et al, 2006b;Stagliano et al, 2006) or were determined as described below. Note that all the compounds shown display anti-HIV activity, except for bis-DKA and 5CITEP (summarized with references in Table 1).…”
Section: Methodsmentioning
confidence: 99%